Strategi Promosi Kredit Usaha Rakyat dalam Meningkatkan Pembiayaan pada Bank Syariah Indonesia KCP Stabat - Sintia, Yulia; Fuadi, Ahmad; Sinaga, Asmawarna (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This research focuses on discussing the promotion of people's business credit financing, obstacles in promoting people's business credit financing products and increasing people's business credit financing with promotional strategies carried out.The research method used in this research is a descriptive qualitative research method with an empirical approach. In this research, researchers used collection techniques, namely by observation, interviews and documentation. Data processing and analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the research explain that the promotion strategy for people's business credit financing carried out by Bank Syariah Indonesia KCP Stabat is by distributing brochures to markets and various places, putting up banners in front of Bank Syariah Indonesia KCP Stabat and certain places, promoting on social media, promoting products in the surrounding environment. , word of mouth promotion, and referrals. There was an increase in people's business credit financing with promotional strategies carried out by Bank Syariah Indonesia KCP Stabat, however the increase was not significant due to increasingly tight competition coupled with the existence of mobile banks and loan sharks. Obstacles in promoting people's business credit financing products at Bank Syariah Indonesia KCP Stabat are the lack of customer interest in people's business credit financing products, customers feel that the requirements for applying for people's business credit are still difficult, there are ordinary customers who compare the processing time at Bank Syariah Indonesia KCP Stabat with banks or other financial institutions, customers do not really need funds for business capital and there is a lack of equipment for customers